Studies on the effect of induced polyploidy on yield and phytochemical content in Centella asiatica (L.) Urban - MR, Rohini; V K, Rao; S, Rajendiran (Journal of Horticultural Sciences, 2024)
Centella asiatica (L.) Urban, family Apiaceae, is a high value medicinal herb cum neutraceutical vegetable. The present investigation has successfully induced tetraploidy in the diploid Centella asiatica variety Arka Prabhavi thereby improving its biomass yield and secondary metabolite yield per unit area. The tetraploid was obtained by treating the shoot tips of diploid genotype (Arka Prabhavi) using 0.05% colchicine via cotton plug method. Tetraploid plants regenerated after six months showed significant changes in morphological traits like stolon length, intermodal length, leaf length, leaf width, petiole length and biomass yield. Tetraploidy was further confirmed with the cytological analysis showing doubling of the number of chromosomes and from the increased stomatal size, decreased stomatal density and increased size of pollen grains. Tetraploid and diploid genotypes were found to be on par for the asiaticoside content (2.37% and 2.30%, respectively) but since the biomass yield was increased (67%), the tetraploid reported 71.7% increase (91.09 kg/ha) in asiaticoside yield over the diploid Arka Prabhavi (53.05 kg/ha). Increase in asiaticoside yield will be beneficial for the pharmaceutical companies and herbal extractors who are interested in higher yield of metabolites in the extract. Analysis of the micronutrient (vitamin and minerals) content in the diploid and teraploid genotype showed significant increase in the tetraploid over the diploid genotype inferring that polyploidization has improved the nutrient levels also making it a promising green leafy vegetable.
Keywords: Arka Prabhavi; Centella asiatica; colchicine; tetraploidy; triterpenoid